Effect of Pyrolysis Atmosphere on the Gasification of Waste Tire Char - Przemysław Grzywacz; Grzegorz Czerski; Wojciech Gańczarczyk (Energies, 2021)
The aim of the study is to assess the influence of the atmosphere during pyrolysis on the course of CO2 gasification of a tire waste char. Two approaches were used: the pyrolysis step was carried out in an inert atmosphere of argon (I) or in an atmosphere of carbon dioxide (II). The examinations were carried out in non-isothermal conditions using a Rubotherm DynTherm thermobalance in the temperature range of 20–1100 °C and three heating rates: 5, 10 and 15 K/min. Based on the results of the gasification examinations, the TG (Thermogravimetry) and DTG (Derivative Thermogravimetry) curves were developed and the kinetic parameters were calculated using the KAS (Kissinger-Akahira-Sunose) and FWO (Flynn-Wall-Ozawa) methods. Additionally, the CO2 gasification of tire chars reaction order (n), was evaluated, and the kinetic parameters were calculated with the use of Coats and Redfern method. Tire waste char obtained in an argon atmosphere was characterized by lower reactivity, which was reflected in shift of conversion and DTG curves to higher temperatures and higher mean values of activation energy. A variability of activation energy values with the progress of the reaction was observed. For char obtained in an argon atmosphere, the activation energy varied in the range of 191.1–277.2 kJ/mol and, for a char obtained in an atmosphere of CO2, in the range of 148.0–284.8 kJ/mol. The highest activation energy values were observed at the beginning of the gasification process and the lowest for the conversion degree 0.5–0.7.